Implementation of the Infrastructure Development Program in the City of Maasin, Southern Leyte: a Case Study - Samaco Jr., Magdaleno T.; Villares, Ofelia A.; Medilo, Jr., Constantino G. (Future Science / FSH-PH Publications, 2023)
SDG No. 9 envisions building resilient infrastructure, promoting inclusive and sustainable industrialization, and fostering innovation. It is congruent with AmBisyon Natin 2040 and Philippine Development Plan which provides a roadmap towards unlocking sustained and inclusive growth for the Philippine economy by accelerating strategic infrastructure development. Hence, this case study was conducted to explore the experiences of the key informants on the Implementation of the Infrastructure Development Program in Maasin City, Southern Leyte as the basis for policy recommendation and theory generation. Utilizing a descriptive-qualitative research design, the data were gathered through an interview with the fourteen key informants and were analyzed following Creswell's six steps in data analysis. The study found that the LGU was able to implement a comprehensive infrastructure development program that fostered economic, social, and environmental sustainability. Generally, the projects were properly implemented by the local officials through the observance of transparency, accountability, and citizen participation. Furthermore, the LGU officials were found to be compliant concerning their financial, managerial, compliance, and result from accountabilities. Although, there were some slight constraints encountered such as non-involvement of private sectors, bureaucratic processes, unprecedented pandemic, and destructive weather conditions, lack of technical skills and qualified manpower, few competent bidders, conflict of interest, political biases, and insufficient resources. Henceforth, the study concludes that the infrastructure development program of Maasin City, Southern Leyte was well implemented and has complied with the basic requirements of RA 9184. A policy recommendation and theory generation were forwarded as the major outputs of the study.